A Comparative Study of Arch Widths of Bangladeshi Subject with Normal Occlusion and Class II Division 1 Malocclusion (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Aim: To evaluate possible differences of the upper and lower dental arches width among youths with Class I,normal occlusion and Class II, division 1 malocclusion. Materials and Methods: The evaluation was conducted on 100 pairs of dental casts of Bangladeshi youths with permanent dentition, 50 with Class I, normal occlusion (22 males and 28 females) at the mean age of 19±3 years and 50 with Class II, division 1, malocclusion (18 males and 32 females ) at the mean age of 20±4 years. The group with Class II malocclusion was divided into two categories: Class II without dental crowding and Class II with dental crowding. A comparison was made between the intercanine inter first premolar and intermolar widths of both dental arches. Results: Subjects with Class II, division, 1 malocclusion when compared with Class I normal occlusion presented (a) in the upper dental arch , smaller intermolar, interpremolar and intercanine width. (b) in the lower dental arch , smaller intermolar width. DOI: http://dx.doi.org/10.3329/bjodfo.v2i2.16159 Ban J Orthod & Dentofac Orthop, April 2012; Vol-2, No.2, 18-23